Structure and function in rhodopsin: the fate of opsin formed upon the decay of light-activated metarhodopsin II in vitro. - Sakamoto, T (1995)
We report that the light-activated bovine metarhodopsin II, upon decay, first forms opsin in the correctly folded form. The latter binds 11-cis-retinal and regenerates the native rhodopsin chromophore. However, when the opsin formed upon metarhodopsin II decay is kept in 0.1% dodecyl maltoside, it converts in a time-dependent manner to a form(s) that does not bind 11-cis-retinal. On subsequent addition of 11-cis-retinal, slow reversal of the non-retinal-binding forms to the correctly folded retinal-binding form has been demonstrated. We have studied the influence, on the above interconversions, of pH, phospholipids (rod outer segment and soybean), dithiothreitol, and a mixture of reduced and oxidized glutathione. Chromophore regeneration in the presence of 11-cis-retinal was highest at pH 6.0-6.3. The addition of dithiothreitol just before bleaching gave back only a small amount (7%) of rhodopsin on the subsequent addition of 11-cis-retinal, whereas the slow phase(s) of chromophore formation was completely abolished. The presence of a mixture of reduced and oxidized glutathione did not significantly affect the results. Addition of phospholipids, either from soybean or rod outer segment, prior to bleaching stabilized the initially formed opsin, resulting in much higher chromophore regeneration. However, addition of the phospholipids after conversion of the opsin to non-retinal-binding form(s) arrested the subsequent reversal of the opsin to the retinal-binding form.